Small Quaternary Inhibitors K298 and K524: Cholinesterases Inhibition, Absorption, Brain Distribution, and Toxicity - Karasova, Jana Zdarova; Hroch, Milos; Musilek, Kamil; Kuca, Kamil (Neurotoxicity research, 2016)
UNLABELLED: Inhibitors of acetylcholinesterase (AChE) may be used in the treatment of various cholinergic deficits, among them being myasthenia gravis (MG). This paper describes the first in vivo data for promising small quaternary inhibitors (K298 and K524): acute toxicity study, cholinesterase inhibition, absorption, and blood-brain barrier penetration. The newly prepared AChE inhibitors (bis-quinolinium and quinolinium compounds) possess a positive charge in the molecule which ensures that anti-AChE action is restricted to peripheral effect. HPLC-MS was used for determination of real plasma and brain concentration in the pharmacokinetic part of the study, and standard non-compartmental analysis was performed. The maximum plasma concentrations were attained at 30 min (K298; 928.76 ± 115.20 ng/ml) and 39 min (K524; 812.40 ± 54.96 ng/ml) after i.m. APPLICATION: Both compounds are in fact able to target the central nervous system. It seems that the difference in the CNS distribution profile depends on an active efflux system. The K524 brain concentration was actively decreased to below an effective level; in contrast, K298 progressively accumulated in brain tissue. Peripheral AChE inhibitors are still first-line treatment in the mild forms of MG. Commonly prescribed carbamates have many severe side effects related to AChE carbamylation. The search for new treatment strategies is still important. Unlike carbamates, these new compounds target AChE via apparent π-π or π-cationic interaction aside at the AChE catalytic site.
Keywords: Blood-Brain Barrier; Cholinesterase Inhibitors; Male; Rats, Wistar; Brain; Cholinesterases; LD50; chinolinové sloučeniny; mužské pohlaví; Myasthenia gravis; potkani Wistar; Preclinical study; krysa rodu Rattus; Quinolinium Compounds; Animals; zvířata; Blood–brain barrier; Small quaternary inhibitors; mozek - chemie; Rats; mozek; Brain Chemistry; cholinesterasy; Lethal Dose 50; Acetylcholinesterase; cholinesterasové inhibitory; hematoencefalická bariéra